ASSESSMENT OF THE QUALITY OF ACCOUNTING OF DEATHS OF PATIENTS WITH MALIGNANT NEOPLASMS IN RUSSIA - G. V. Petrova; V. V. Starinskiy; O. P. Gretsova (Исследования и практика в медицине)
It is presented the comparative assessment of the quality of the records of patients who died from malignant neoplasms (MN), according to the report of Rosstat used to calculate mortality rates (form No. 5 “the Distribution of deaths by sex, age groups and causes of death”), and according to the report of the Ministry of health (form № 35 “Data on patients with malignant neoplasms”), used to calculate the mortality rate of patients under medical observation. Improving the quality and completeness of information about cancer patients is associated not only with the necessity of improving the accounting system, but with a best option compared with the most used in the world practice, as with any organizational issues.The following materials will be used. Rosstat data:• the distribution of deaths from MN by age and sex (form No. 5);• average annual number of population in administrative territories of Russia. The data of the Ministry of health (form No. 35):• the number of deaths from the MN from the number taken into account;• the number of deaths from the MN, not consisting on the account of cancer institution, including:– with the diagnosis established postmortem, including autopsy;– consisted on the account in medical institutions of other ministries and departments;• the number of deaths (from those considered), the cause of death was non-oncological disease;• the number of deaths from complications related to the treatment (from the number registered during the previous year and died from the MN).The study was conducted with the use of information and analytical support of the database on Oncology on the basis of state statistical reporting, created by P. Herzen MORI.